Potentiometric Analysis of Samarium Ion in Aqueous Solution Employing Selective Electrode Based on Crown Ethers - Samarium Picrate Complexes in a PVC Membrane - Karim, N. H.; AI- Nuaimi, S.A.; Nassory, N. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Samarium  ion selective  electrodes  we1Â·e  construct.ed  and  preparedthen  tested as  probefor  Samarium  ion detection  and determination  in different aqueous solutions.The sensitive membrane is made of  PVC which contains Samariumpicrate complexed with either 18-crown-6 or 15-crown-5 ethers as active species.Different  plasticizers:  phthalates  (DBPH),  phosphates  (DBP)  andphosphonates  (DOPP) were incorporated into the membranes as solventmediators.Every   membrane   was   evaluated   practically   following   standardproced ures to find out its reliability and durability as a probe suitable for analytical application.Linear working range, Ncrnestain slope, detection l imit, measurement stability, response time  and electrode  l ife tirnc were calculated  for each electrode.The l inear concentration range for most ol'the electrodes were from-      _,10 to 10 molar Sm (III), the slope was 18 mv/decade to 20 mv/decade whi l ethe working pH range was from 3 to 8.Cations interference and anion radicals Na+, Ca2+, La"+, Nd '+ haveno effect on the measurement selectivity except  in the presence M (Ill)ions.